The effects of necrostatin‐1 on the in vitro development and function of young porcine islets over 14‐day prolonged tissue culture. (12th January 2021) - Lau, Hien; Corrales, Nicole; Rodriguez, Samuel; Park, Soomin; Mohammadi, Mohammadreza; Li, Shiri; Alexander, Michael; Lakey, Jonathan R.T.
Abstract: Background: Necrostatin‐1 (Nec‐1) supplementation to tissue culture media on day 3 has recently been shown to augment the insulin content, endocrine cellular composition, and insulin release of pre‐weaned porcine islets (PPIs); however, its effects were only examined for the first 7 days of tissue culture. The present study examined whether the addition of Nec‐1 on day 3 could further enhance the in vitro development and function of PPIs after 14 days of tissue culture. Methods: PPIs were isolated from 8‐ to 15‐day‐old, pre‐weaned Yorkshire piglets and cultured in an islet maturation media supplemented with Nec‐1 on day 3. The recovery, viability, insulin content, endocrine cellular composition, GLUT2 expression in beta cells, differentiation and proliferation potential, and glucose‐stimulated insulin secretion of PPIs were assessed on days 3, 7, and 14 of tissue culture (n = 5 on each day). Results: Compared with day 7 of tissue culture, islets on day 14 had a lower recovery, GLUT2 expression in beta cells, proliferation capacity of endocrine cells, and glucose‐induced insulin stimulation index. Prolonging the culture time to 14 days did not affect islet viability, insulin content, proportion of endocrine cells, and differentiation potential. Conclusion: The growth‐inducing effects of Nec‐1 on PPIs were most effective on day 7 of tissue culture when added on day 3. Our findings support existing evidence that the in vitro activities of Nec‐1 are short‐lived and encourage future studies to explore the use of other novel growth factors during prolonged islet tissue culture.